Deskripsi Pembelajaran Tari Gending Sriwijaya pada Kelas XI di SMA Negeri 8 Palembang di Masa Pandemi Covid-19 - Indasari, Mesi; Dessy Wardiah, Dessy Wardiah; Nurdin, Nurdin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
Gending Sriwijaya dance learning is carried out through online and offline learning where students are divided 50% online and 50% offline. The problem in the study is how to describe the learning of Sriwijaya Gending Dance in class XI at SMA Negeri 8 Palembang through online and offline learning during the Covid-19 pandemic. The purpose of this study is to describe how to prepare for the implementation and evaluation of learning Gending Sriwijaya Dance in class XI at SMA Negeri 8 Palembang. The research method used is descriptive qualitative method with data collection techniques used are observation, interviews and documentation. The subjects in this study were teachers and students. The activity stage in the learning process of Gending Sriwijaya dance includes preparation, implementation and evaluation of learning.